A Highly Stable Bimetallic Transition Metal Phosphide Catalyst for Selective Dehydrogenation of n-Heptane - Stöber, Robert; Mai, Florian; Oshin, Oshin; Körner, Andreas; Hutzler, Andreas; Schühle, Patrick (ChemCatChem, 2022)
In this work, we demonstrate RuP2-MoP catalysts being highly stable and selective for the dehydrogenation of long-chain alkanes like n-heptane. Compared to a monometallic MoP catalyst, the bimetallic system substantially increases n-heptene selectivity from 40 % towards 80 %. This effect can be traced back to a reduced surface acidity, suppressing the competitive hydrogenolysis reaction. The active transition metal phosphide is, furthermore, compared to its phosphorous-free RuMo-counterpart. As revealed by STEM-EDX investigations, incorporation of phosphorous results in the formation of separated metal phosphide clusters instead of an intermetallic alloy. In the dehydrogenation of n-heptane the phosphorous modification clearly avoids catalyst deactivation and maintains the high n-heptene selectivity. X-ray diffraction, elemental analysis and STEM-EDX further reveal that catalyst coking and the formation of less active molybdenum carbide phases is effectively suppressed by phosphorous incorporation, making RuP2-MoP an attractive system for selective dehydrogenation of long-chain alkanes.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Alkane dehydrogenation; Coking resistance; Heterogeneous catalysis; Molybdenum catalyst; Transition metal phosphides